Peningkatan Hasil Belajar Keliling dan Luas Bangun Datar dengan Pendekatn Pendidikan Matematika Realistik Indonesia (PMRI) di Kelas Iv Sdn 14 Koto Lalang Kota Padang - Latifatu Qolbi; Masniladevi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to improve students' learning outcomes through the implementation of the Indonesian Realistic Mathematics Education (RME) approach. The study employed qualitative and quantitative approaches using Classroom Action Research (CAR), conducted in three cycles consisting of planning, action, observation, and reflection. The participants were 27 fourth-grade students. Data were collected through observations, interviews, and learning outcome tests using Deep Learning Lesson Plan observation sheets, teacher and student activity observation sheets, and evaluation questions. Qualitative analysis described the learning process, while quantitative analysis measured improvements based on average scores and mastery percentages. The findings showed improvements in all aspects. The RPM implementation score increased from 81.25% to 89.59% and 95.83%. Teacher and student activity scores improved from 82.14% to 91.08% and 96.43%. The average learning outcome score increased from 70.68 to 81.41 and 95.87. Therefore, the implementation of the PMRI approach effectively improved the mathematics learning outcomes of fourth-grade students.